2018
DOI: 10.1177/1098612x18757602
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of 152 feline cytological bone marrow examinations: preliminary classification and ranges

Abstract: This study provides a general overview of the prevalence and incidence of feline bone marrow disorders together with ranges for differential nucleated cell counts and M:E ratios for the various conditions reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
9
2
1
Order By: Relevance
“…There was no statistical association between the leukogram results and retroviral infection, reinforcing the hypothesis of the absence of bone marrow involvement. Changes in the total leukocyte count are related to the reduction in the number of circulating neutrophils, mainly in the acute phase of infections and later in the immunosuppression phase, due to insufficient myelopoiesis (Shelton et al, 1990;Costa et al, 2017;Turinelli & Gavazza, 2018). Lymphopenia is related to the onset of immunosuppression, with a decrease in the number of CD4 and CD8 cells (Hofmann-Lehmann et al, 1997;Novo et al, 2016;Little et al, 2020 Regarding biochemical changes, we observed a tendency towards hyperproteinemia in FIV positive cats.…”
Section: Discussionmentioning
confidence: 77%
“…There was no statistical association between the leukogram results and retroviral infection, reinforcing the hypothesis of the absence of bone marrow involvement. Changes in the total leukocyte count are related to the reduction in the number of circulating neutrophils, mainly in the acute phase of infections and later in the immunosuppression phase, due to insufficient myelopoiesis (Shelton et al, 1990;Costa et al, 2017;Turinelli & Gavazza, 2018). Lymphopenia is related to the onset of immunosuppression, with a decrease in the number of CD4 and CD8 cells (Hofmann-Lehmann et al, 1997;Novo et al, 2016;Little et al, 2020 Regarding biochemical changes, we observed a tendency towards hyperproteinemia in FIV positive cats.…”
Section: Discussionmentioning
confidence: 77%
“…5,6 Erythroid hypoplasia was defined as a normal or decreased BM cellularity with an M:E ratio above 2.16. 5 Pure red cell aplasia was defined as a severe increase in the M:E ratio above 75:1 along with a non-regenerative anaemia. 6 Medical records were reviewed for those cases that had BM cytology and/or histology available.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of diagnosis, BM samples were microscopically evaluated (including a differential cell count). The BM samples were classified as erythroid hyperplasia when cellularity was normal or increased and the myeloid:erythroid (M:E) ratio was below 1.2 5,6 . Erythroid hypoplasia was defined as a normal or decreased BM cellularity with an M:E ratio above 2.16 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Em outro estudo, apenas 16% dos gatos com LLA apresentaram linfocitose acentuada (mais de 14.000 céls/μL), mas apesar de uma quantidade semelhante de células por µL a(HARVEY, 2012;TURINELLI & GAVAZZA, 2018). Contudo, neste estudo, foram encontrados blastos no sangue de apenas três dos gatos, que representaram os únicos com linfocitose superior a 100.000/µL, podendo indicar quadro mais avançado.…”
unclassified